The Mechanism of Alisol B23 Acetate Inhibiting Lung Cancer: Targeted Regulation of CD11b/CD18 to Influence Macrophage Polarization - Chen Y; Lu J; Xie Z; Tang J; Lian X; Li X (Dove Medical Press, 2022)
Yingna Chen,1 Jieya Lu,2 Zhihao Xie,1 Jialing Tang,1 Xuejiao Lian,1 Xiuwen Li1 1School of Pharmacy, School of Medicine, Changzhou University, Changzhou, Jiangsu, People's Republic of China; 2Department of Nephrology, Yixing Hospital of Traditional Chinese Medicine, Yixing, Jiangsu, People's Republic of ChinaCorrespondence: Yingna Chen, School of Pharmacy, School of Medicine, Changzhou University, No. 21, Lake Gehu Road, Wujin District, Changzhou, Jiangsu, People's Republic of China, Tel +86-13813661630, Email chenyingna@cczu.edu.cn Jieya Lu, Department of Nephrology, Yixing Hospital of Traditional Chinese Medicine, 128 Yangquan East Road, Yicheng Street, Yixing, Jiangsu, People's Republic of China, Tel +86-15906153777, Email ljy7011645@sina.comBackground: Tumor microenvironment has attracted more and more attention in oncology. Alisol B23 acetate (AB23A) inhibits the proliferation of tumor cells including non-small cell lung cancer (NSCLC) cells. However, whether AB23A plays a role in the tumor microenvironment of NSCLC still remains obscure.Methods: After THP-1 cells were polarized to M0 type by PMA, M0 macrophages were differentiated into M1 by LPS and IFNγ, and were differentiated into M2 by IL-4 and IL-13. The differentiation of THP-1 cells was detected by flow cytometry. After AB23A was given to macrophage RT-qPCR and ELISA detected the expressions of IL-6, IL-1β, IL-10 and TGF-β. Western blot and RT-qPCR detected the expressions of CD11b and CD18 at both mRNA and protein levels. Lung cancer cell A549 cells were induced by above related macrophage culture medium. Cell proliferation was detected by CCK-8. Tunel, wound healing and Transwell detected the apoptotic, migration and invasion capabilities. Next, M0 and M1-type macrophages were cultured in the cell culture medium of conventional A549 cells, to which AB23A was added. Subsequently, cell differentiation and inflammatory response were measured. Finally, the expression of CD18 in A549 cells was knocked down to construct NSCLC tumor-bearing mice and AB23A was applied for intragastric administration. Immunohistochemistry detected the polarization of macrophages in tumor tissues. Western blot detected the expressions of CD11b, CD18, invasion-, migration- and apoptosis-related proteins.Results: AB23A promoted the polarization of macrophages towards M1, thus promoting the apoptosis and inhibiting the invasion and migration of A549 cells. The tumor cell culture medium induced M0 macrophages to M2, while AB23A reversed this effect. AB23A targeted CD11b/CD18 and improved the polarization of macrophages, thereby affecting tumor invasion, migration and apoptosis.Conclusion: AB23A affected the polarization of tumor-associated macrophages through the targeted regulation of CD11b/CD18, thus inhibiting the development of lung cancer.Keywords: Alisol B23 acetate, lung cancer, CD11b/CD18, tumor microenvironment